The Use of Nutritional Rice Specific Resistance for Control of Pathogen Pyricularia oryzae - Santoso Santoso; Ratna Sari Dewi; Anggiani Nasution; Heni Safitri; Puji Lestari (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Apart from being a source of energy, rice is also a source of protein and microelements that are useful for human health, such as B vitamins, iron (Fe), zinc (Zn), anthocyanins, and folic acid. Blast disease caused by the fungus Pyricularia oryzae is an important disease in rice crops worldwide. The aim of the study was to evaluate the resistance of nutritionally specific rice lines to blast disease. The nutritionally specific rice tested were preliminary yield lines and multilocation trials. The pathogens of P. oryzae used were 4 races, namely races 173, 133, 073 and 033. Observations and analysis of resistance to blast disease were carried out based on the IRRI SES method. The results for the preliminary yield trial line showed that the B15068C-MR-1-2-7-KN-2 line showed a resistant response to 4 races of blast pathogen with a disease scale of 1 and as many as 11 special rice lines showed a resistant response or moderately resistant to 4 races, while the multilocation trial lines obtained as many as 3 special rice lines and the variety of Inpari 19 which had a resistant or moderately resistant response to 4 races of P. oryzae. These nutritionally specific rice lines can be used as gene donors for resistance or proposed as varieties that have blast disease resistance. while the multilocation trial lines obtained as many as 3 special rice lines and the variety of Inpari 19 which had a resistant or moderately resistant response to 4 races of P. oryzae. These nutritionally specific rice lines can be used as gene donors for resistance or proposed as varieties that have blast disease resistance. while the multilocation trial lines obtained as many as 3 special rice lines and the variety of Inpari 19 which had a resistant or moderately resistant response to 4 races of P. oryzae. These nutritionally specific rice lines can be used as gene donors for resistance or proposed as varieties that have blast disease resistance.